Occurrence and Variability of the Efflux Pump Gene norA across the Staphylococcus Genus - Ferreira, Carolina; Abrantes, Patrícia; Costa, Sofia Santos; Viveiros, Miguel; Couto, Isabel (International journal of molecular sciences, 2022)
NorA is one of the main native MDR efflux pumps of Staphylococcus aureus, contributing to reduced susceptibility towards fluoroquinolones and biocides, but little is known about its variability within S. aureus or its distribution and conservation among other staphylococci. We screened for sequences homologous to S. aureus norA and found it in 61 out of the 63 Staphylococcus species described. To the best of our knowledge, this is the first study to report the occurrence of norA across the Staphylococcus genus. The norA phylogenetic tree follows the evolutionary relations of staphylococci and the closely related Mammalliicoccus genus. Comparative analyses suggest a conservation of the NorA function in staphylococci. We also analyzed the variability of norA within S. aureus, for which there are several circulating norA alleles, differing up to 10% at the nucleotide level, which may hamper proper norA detection. We demonstrate the applicability of a PCR-based algorithm to detect and differentiate norA alleles in 52 S. aureus representing a wider collection of 89 isolates from different hosts. Our results highlight the prevalence of norAI and norAII in different settings and the association of norA alleles with specific S. aureus clonal lineages. Ultimately, it confirms the applicability of our PCR-based algorithm to rapidly detect and assign the different norA alleles, a trait that may impact antimicrobial efflux capacity and the search for potential NorA inhibitors.